Outbound tourism by the physically disabled inhabitants of Kraków: current situation and future needs - Furmanek, Mirosław (Turyzm/Tourism, 2014)
The article is an analysis of outbound tourism by those with locomotor disabilities living in Kraków. Two aspects were compared: their tourism activity before and after the occurrence of the disability. The article describes seasonality, length of stay and destinations, limitations encountered, preferred forms of tourism, organisation of travel, preferred accommodation, means of transport and expenditure. It also presents motivations, expectations and the impact of their experience on future travel behaviour.